Cybergogy-Assisted E-Module to Boost Middle Schoolers’ Digital Literacy in the Mixture Separation Topic - Ramadhani, Novitasari; Subekti, Hasan (Lafadz Jaya Publisher, 2025)
This study aims to describe the effect of a cybergogy-based approach supported by an e-module in fostering students’ digital literacy on the topic of mixture separation. Motivated by the demands of Industry 4.0/Society 5.0 and low literacy outcomes (e.g., PISA 2022) as well as preliminary findings at SMP Negeri 1 Bagor—where only 50% of students surpassed the Minimum Mastery Criterion (KKM) of 70 in science—the research employed a pre-experimental one-shot case study design with 32 Grade VIII-D students. Digital-literacy performance was measured through a verified posttest and analyzed descriptively and inferentially. Shapiro–Wilk testing indicated non-normality, so a Wilcoxon test was conducted against the KKM benchmark. The mean posttest score was 82.28 (min 75.00; max 91.66), with average achievement across components of 79% (high category); hypertext navigation was the strongest component (94%, very high), while content evaluation was the weakest (64%, high). The Wilcoxon test yielded Asymp. Sig (2-tailed) < 0.001, indicating a significant improvement relative to the benchmark. These findings suggest that the cybergogy-assisted e-module is effective for cultivating students’ digital literacy in mixture separation, with device-access constraints noted as a practical limitation for future implementations.